Fabrication and Preliminary In Vitro Evaluation of 3D-Printed Alginate Films with Cannabidiol (CBD) and Cannabigerol (CBG) Nanoparticles for Potential Wound-Healing Applications - Paraskevi Kyriaki Monou; Anastasia Maria Mamaligka; Emmanuil K. Tzimtzimis; Dimitrios Tzetzis; Souzan Vergkizi-Nikolakaki; Ioannis S. Vizirianakis; Eleftherios G. Andriotis; Georgios K. Eleftheriadis; Dimitrios G. Fatouros (MDPI AG, 2022)
In this study, drug carrier nanoparticles comprised of Pluronic-F127 and cannabidiol (CBD) or cannabigerol (CBG) were developed, and their wound healing action was studied. They were further incorporated in 3D printed films based on sodium alginate. The prepared films were characterized morphologically and physicochemically and used to evaluate the drug release profiles of the nanoparticles. Additional studies on their water loss rate, water retention capacity, and 3D-printing shape fidelity were performed. Nanoparticles were characterized physicochemically and for their drug loading performance. They were further assessed for their cytotoxicity (MTT Assay) and wound healing action (Cell Scratch Assay). The in vitro wound-healing study showed that the nanoparticles successfully enhanced wound healing in the first 6 h of application, but in the following 6 h they had an adverse effect. MTT assay studies revealed that in the first 24 h, a concentration of 0.1 mg/mL nanoparticles resulted in satisfactory cell viability, whereas CBG nanoparticles were safe even at 48 h. However, in higher concentrations and after a threshold of 24 h, the cell viability was significantly decreased. The results also presented mono-disperse nano-sized particles with diameters smaller than 200 nm with excellent release profiles and enhanced thermal stability. Their entrapment efficiency and drug loading properties were higher than 97%. The release profiles of the active pharmaceutical ingredients from the films revealed a complete release within 24 h. The fabricated 3D-printed films hold promise for wound healing applications; however, more studies are needed to further elucidate their mechanism of action.